Dealing with the Experimenter Effect - Bierman, Dick; Jolij, Jacob J. (Journal of Scientific Exploration, 2020)
Methods in experimental science assume objective facts, and those effects are generally independent of the observer or experimenter. This objectivity assumption is not warranted in the field of human studies. Results of psychological experiments tend to be dependent on among other things the expectations of the experimenter. The experimenter effect togther with the replication crisis in social psychology are major issues in experimental parapsychology. We use Houtkooper's Hierarchical Observational Theory to look at a model for dealing with this issue, and conclude that multiple-experimenter projects might be able to sort out experimenter effects from intrinisic effects. Keywords: experimenter effect; replication crisis; psi; parapsychology